LATENT AUTOIMMUNE DIABETES IN YOUTH PRESENTING AS YOUNG-ONSET TYPE 2 DIABETES: A CASE REPORT - Putra, Khoirun Mukhsinin; Kusnadi, Yulianto; Dewi, Ratna Maila; Shahab, Alwi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Latent autoimmune diabetes forms a continuous age-related spectrum from LADY to LADA, where LADY exhibits greater autoimmunity. Latent autoimmune diabetes in youth (LADY) is diagnosed in individuals aged 15 to 29 years. A high prevalence of LADY is observed among youth with the T2DM phenotype. The TCF7L2 rs12255372 polymorphism is linked to an increased risk of developing T2DM at a young age and is associated with lower levels of GADA in individuals with either T2DM or latent autoimmune diabetes. CASE A 28-year-old female with no history of T2DM was admitted to the emergency room due to altered mental status. She had experienced a weight loss of approximately 10 kg and frequent nocturnal urination; however, she had never consulted a physician. Both her parents and her sister have a known history of T2DM. A physical examination revealed excess body weight and acanthosis nigricans. Laboratory results indicated elevated glucose levels, a high A1C level, a normal fasting C-peptide, negative ketones in the urine and a high HOMA-IR score. Following the patient’s clinical improvement, we transitioned from insulin to oral hypoglycemic drugs. After several weeks, we identified a positive anti-GAD result and the TCF7L2 gene polymorphism, rs12255372 (G/T). CONCLUSION The clinical diagnosis of latent autoimmune diabetes (LAD) can be quite challenging. Young individuals exhibiting a T2DM phenotype should undergo assessment for pancreatic islet cell autoantibodies. Common TCF7L2 gene polymorphisms are linked to T2DM and latent autoimmune diabetes but not type 1 diabetes.